Mechanical characterization of an endoprosthesis. - Tan, Xue Yu. (2009)
Loss of mandibular bone as a result of trauma, inflammatory diseases and benign or malignant tumors demonstrated the need of mandibular reconstruction. The recent success of Tideman Lee’s modular endoprosthesis had been populated as a successful method of mandibular reconstruction. The objective of this study was to identify the bite force, fracture load, strain distributions and to make comparisons on how this property differs between normal and reconstructed mandible. In addition, fatigue behaviors of intact mandibles were examined in this work. For this study, a novel testing rig was also designed to facilitate the in vitro experimental test.